REKONSTRUKSI FUNGSI PENGAWASAN SYAHBANDAR TERHADAP PRAKTIK SHIP-TO-SHIP TRANSFER (STS) ILEGAL DALAM PENGANGKUTAN BBM BERSUBSIDI: ANALISIS NORMATIF ATAS KESENJANGAN PENGATURAN HUKUM - Karso Raharjo; Kuat Puji Prayitno; Dwi Hapsari Retnaningrum (Universitas Labuhanbatu, 2026)
Illegal ship-to-ship transfer (STS) practices involving subsidized fuel oil constitute a significant legal challenge because they facilitate the unlawful diversion of subsidized energy distribution, potentially causing state financial losses and undermining national energy policies. Although Indonesian Shipping Law authorizes the Harbormaster (Syahbandar) to supervise maritime activities, the existing legal framework remains primarily focused on navigational safety and administrative compliance, leaving substantive cargo legality and offshore STS activities largely beyond its regulatory reach. This study aims to analyze the legal construction of the Harbormaster's supervisory authority over illegal STS practices involving subsidized fuel transportation and to formulate directions for strengthening the existing regulatory framework. The research employs a normative legal method using statutory and conceptual approaches by examining the Shipping Law, Government Regulation Number 31 of 2021, and other relevant legal instruments governing subsidized fuel distribution. The collected legal materials were analyzed qualitatively through systematic legal interpretation. The findings reveal that the Harbormaster's supervisory authority is limited to administrative verification of vessel documents and does not extend to verifying cargo legality or tracing vessel movement history. This normative limitation creates legal loopholes that enable illegally transferred subsidized fuel cargoes to enter the port system through formally valid documentation. This study proposes strengthening the legal construction of the Harbormaster's supervisory function by expanding the scope of supervision, integrating maritime and energy regulatory frameworks, reinforcing inter-agency coordination, and introducing substantive cargo verification mechanisms to prevent the misuse of subsidized fuel distribution.Keywords: Harbormaster; ship-to-ship transfer; subsidized fuel; maritime supervision; legal construction